Associations between the Canadian 24 h movement guidelines and different types of bullying involvement among adolescents. (October 2020) - Sampasa-Kanyinga, Hugues; Colman, Ian; Goldfield, Gary S.; Janssen, Ian; Wang, JianLi; Hamilton, Hayley A.; Chaput, Jean-Philippe
Abstract: Background: The Canadian 24-Hour Movement Guidelines for Children and Youth recommend ≥60 min of physical activity per day, ≤2 h of recreational screen time per day, and 9−11 hours of sleep per night for 11–13 years old and 8−10 hours per night for 14–17 years old. Objective: This study examined the association between combinations of these recommendations and school bullying and cyberbullying victimization and perpetration among adolescents. Participants and Setting: A total of 5615 Canadian students (mean age = 15.2 years) who participated in the 2017 Ontario Student Drug Use and Health Survey (OSDUHS) self-reported their physical activity, screen time, sleep duration, and their involvement in bullying. Methods: Logistic regression analyses were adjusted for important covariates. Results: Meeting the screen time recommendation alone was associated with lower odds of being a victim (OR: 0.64; 95 % CI: 0.46−0.88) or a bully (OR: 0.64; 95 % CI: 0.43−0.96) at school and a victim of cyberbullying (OR: 0.67; 95 % CI: 0.49−0.91). Meeting both the screen time and sleep duration recommendations was associated with lower odds of being a bully (OR: 0.51; 95 % CI: 0.30−0.88). Meeting all 3 recommendations showed stronger associations (i.e. lowest risk) with being a victim of school bullying (OR: 0.32; 95 % CI: 0.19−0.54), a bully-victim (OR: 0.25; 95 % CI: 0.08−0.78) or a victim of cyberbullying (OR: 0.37; 95 % CI: 0.17−0.84). Conclusions: Our findings provide evidence that meeting the 24 -h movement guidelines is associated with lower odds of bullying involvement. Encouraging adherence to the 24 -h movement guidelines could be a good behavioural target to prevent involvement in both school bullying and cyberbullying.